Human development in South Asia 2002 (Oxford University Press,The Mahbub ul Haq Human Development Centre, 2003)
This report is about agriculture and its link to human wellbeing in South Asia. This report presents an in-depth analysis of the experience of five South Asian countries: Indian, Bangladesh, Pakistan, Nepal and Sri Lanka